CBS News National Surveys, 1985 ([Verlag nicht ermittelbar], 1986)
Each dataset contains questions of topical relevance or questions which pertain to broader social issues. The hijacking of TWA flight 847 was the focus of the first two surveys. Respondents were asked to evaluate Reagan's handling of the crisis, to give their opinions on how the United States should deal with terrorism and terrorists, and to explain their attitudes about United States policy in the Middle East and media coverage of the event. Attitudes towards air safety, including effects on travel plans, were explored in the third survey. The fourth dealt with the United States/Soviet summit meeting in Geneva. Questions regarding the summit include approval or disapproval of Reagan's handling of the summit, whether and how to negotiate with the Soviet Union, attitudes towards Gorbachev, and the role the leaders' wives played. In the final survey, respondents were queried about professional football--the game, teams, players, coaches, and media coverage. All respondents were asked for demographic information.